The Extent to Which Hour of Code with Minecraft Achieved the Sultanate of Oman’s Child-Friendly Education Principles (The International Journal of Educational Sciences and Arts, 2025)
The study aimed to evaluate the extent to which the "Hour of Code" with Minecraft initiative could achieved the Sultanate of Oman’s child-friendly education principles, in accordance with the Child-Friendly Education Guide issued by the Ministry of Education and UNICEF (2022). The sample included 62 teachers and 2,353 students from the third and fourth grades in schools in Dhofar Governorate. The study used a form to collect data on the implementation of the Hour of Code with Minecraft and a 20-item questionnaire for teachers, measuring the achievement of the six principles of child-friendly education: equality, child-centeredness, participation, sustainability, inclusivity, and protection.The study showed that the program highly achieved the child-centeredness principle, as it encouraged students to make independent decisions and develop critical thinking. There was also a high level of achievement in the principles of equality and protection. However, there was a relative weakness in the participation principle, especially in involving parents. The results also indicated that the program was inclusive, providing equal opportunities for children to participate regardless of their economic or social backgrounds. There was no significant effect of the schools' geographic location from the governorate center on the implementation of activities or the achievement of principles, reflecting the program’s effectiveness in providing equal educational opportunities for children, It also indicates the readiness of the necessary infrastructure for e-learning based on Internet communication in Dhofar Governorate, as well as a high level of sustainability and adaptability.The study recommends enhancing parental involvement in various educational activities, developing comprehensive teacher training on implementing child-friendly education principles through educational activities, and establishing these principles as foundational in designing educational programs. Additionally, it suggests improving technological resources in remote schools and adopting the Hour of Code with Minecraft as part of the school curriculum.
Keywords: Child-Friendly Education; Hour of Code with Minecraft; Oman’s Child-Friendly Education Principles; STEM Education; Teaching Programming